Geliat Surat Kabar Harian Olahraga di Indonesia - MAHENDRA, NARAYANA MAHENDRA PRARSTYA PRARSTYA (Universitas Muhammadiyah Yogyakarta, 2014)
The publishing of sports daily newspaper in Indonesia begins to show significant progress. In the past two years, two sports daily newspapers namely Harian Bola and SuperBall appeared. Both these daily newspapers followed the sports daily newspaper TopSkor who was published earlier. Sports daily newspapers in Indonesia currently exist in the middle of the condition when the number of newspapers readers is decreasing. However, sport daily newspapers can also have a good prospect if it is managed properly. This paper provides a preliminary review of the three sports daily newspapers in Indonesia namely TopSkor, Harian Bola, and SuperBall. The focus is on the content, structure, behavior, and performance or S-C-P (structure-conduct-performance). In this review, the author provides recommendations about what should be done by the sports daily newspapers. In the conclusion, the author gives recommendations on further studies which can be done regarding to sports daily newspapers in Indonesia. Keywords: sports media, sports news, structure, conduct, performance